A randomised controlled trial of outpatient compared with inpatient cervical ripening with prostaglandin E2 (OPRA study). (14th May 2014) - Wilkinson, C; Bryce, R; Adelson, P; Turnbull, D
<x xml:space="preserve">Abstract</x> Objective To compare clinical outcomes from outpatient with inpatient cervical prostaglandin E2 ripening for low risk labour induction. Design Randomised controlled trial. Setting Two tertiary hospitals in Adelaide, Australia. Population Women with uncomplicated term pregnancies, scheduled for induction of labour for reasons of post‐dates or for social reasons. Methods Eight hundred and twenty‐seven women were randomised at induction decision to an outpatient or inpatient group. All women had CTG monitoring before and after vaginal PgE2 administration. The inpatient women were admitted and the outpatient group was discharged home overnight with instructions to return if labour established or rupture of membranes occurred. Next morning, outpatient women were admitted for rupture of membranes or further ripening. After membrane rupture, both groups received routine care. Main outcome measures Oxytocin use, maternal and fetal outcomes, and whether planned outpatient management was achievable. Results There were no significant differences in oxytocin use (2.5% difference, CI−4.3 to 9.4), caesarean sections (−0.59% difference, CI−6.3 to 5.1), epidural use (1.5% difference, CI−5.1 to 8.2), vaginal delivery within 24 hours (−8.2% difference, CI−17.6 to 1.3) or labour complications. More than half of the randomised women did not receive the intervention as they laboured spontaneously, or did not require ripening. The post‐hoc analysis of women who received ripening also indicated no statistically significant differences in the patterns or results, with the exception of outpatient women having a longer mean length of active labour (mean difference 66 minutes, CI 4–128 minutes). Outpatient women who received ripening were diagnosed more frequently with non‐reassuring CTG monitoring and hyperstimulation, with less than half of the women going home and remaining home overnight. Conclusions This study demonstrated no clinical advantage or disadvantage in prostaglandin E2 outpatient cervical ripening. Uterine stimulation following prostaglandins may preclude a woman from going home or remaining at home overnight and may not be the best agent for outpatient ripening.